2012
DOI: 10.1063/1.4763984
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of structural and dynamic anisotropy in nano-confined water between parallel graphite plates

Abstract: We use molecular dynamics simulations to study the structure, dynamics, and transport properties of nano-confined water between parallel graphite plates with separation distances (H) from 7 to 20 Å at different water densities with an emphasis on anisotropies generated by confinement. The behavior of the confined water phase is compared to non-confined bulk water under similar pressure and temperature conditions. Our simulations show anisotropic structure and dynamics of the confined water phase in directions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
88
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 65 publications
15
88
1
Order By: Relevance
“…Computational studies agree that under two-dimensional nanoconfinement water is structured into layers perpendicularly oriented with respect to the confining direction (monolayer [10][11][12][13][14][15][16][17][18], bilayer [19][20][21][22][23][24][25][26][27][28][29], trilayer and so on [30][31][32][33][34]). Most of the computational studies agree with the existence of a stable monolayer square ice phase [10][11][12][13].…”
Section: Introductionmentioning
confidence: 72%
“…Computational studies agree that under two-dimensional nanoconfinement water is structured into layers perpendicularly oriented with respect to the confining direction (monolayer [10][11][12][13][14][15][16][17][18], bilayer [19][20][21][22][23][24][25][26][27][28][29], trilayer and so on [30][31][32][33][34]). Most of the computational studies agree with the existence of a stable monolayer square ice phase [10][11][12][13].…”
Section: Introductionmentioning
confidence: 72%
“…Contrary to the TEM experiments, those simulations indicate an FCC-like lattice. Given the setup of the simulations, we believe that this FCC structure may have been related either to ice VI, or to the rhombic structure found at extremely low pressure in other simulations 12 . While the authors of Ref.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found that when water is confined between graphene sheets or graphite, there is clear structure in the direction normal to the surfaces but the in-plane order is typically either liquid-like or hexagonal. In the case of the hexagonal structure there are, however, different opinions on whether or not it is related to the graphite structure 12,14 . Confinement is, however, not required for the hexagonal structure to develop under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the hydration shell of the sodium ion is more labile than that of calcium ions. Previous computational studies showed that in nanoconfined environments the diffusion of water is considerably slower than in the bulk [63,64]. However, compared with simulations of graphene oxide layers [63], where the water diffusion in a layer spacing of 15 Å converged to that of bulk water, in the HAP (H = 110 Å)-water system the value of D W (19.3 × 10 −10 m 2 ·s −1 ) is still 15% lower than in the bulk water (see Table 3).…”
Section: Number Of Hydrogen Bonds (%)mentioning
confidence: 99%